MODIFIKASI UNIT CV 507 DENGAN MENAMBAHKAN BYPASS CHUTE DAN PENYARING (SCREEN SIZER) SEBAGAI PEMISAH UKURAN BATUBARA - Susanti Sundari; Ikri Karwana (Fakultas Teknik Universitas Tulang Bawang Lampung, 2018)
This study discussed about modifying coal storage units which function to separate large size coal, pack stones, which causes the carrying capacity of coal to ships or stock piles not to reach maximum capacity. This is due to the inability of the CV507 line to load coal in accordance with design capacity Shiploader 2 which is 6000 tons / hour maximum. the operational and financial impacts caused by large coal or pack stones can cause the unit to disassemble to be disrupted or damaged and the capacity is not optimal. The current target set is the loading of coal loads can exceed 1,350,000 tons per month. The method used in identifying cases is reviewed from the QCDSMP method (Quality, Cost, Delivery, Safety, Morale, Productivity) used in the company, and analysis of the cause of this case using the Fish Bone method to determine dominant cause factors. From the results it is known that the most dominant causative factor is the Method, where there must be a separation process between large and small coal in the Screen Sizer before the Auxiliary Screen, so that the coal according to the screen size is directed directly to CV508 without passing through the large Auxiliary Screen and big coal (oversize) through the Auxiliary Screen process to be separated so as not to enter to the ship by modifying the CV507 unit.